Low-dose aspirin and the severity of ıschemic colitis: A single-center retrospective study - Dacheng Wu,; Guotao Lu,; Guotao Lu,; Yanbing Ding,; Yanbing Ding,; Weijuan Gong,; Weijuan Gong,; Yuanzhi Wang,; Yuanzhi Wang,; Weiming Xiao,; Dacheng Wu,; Bin Deng,; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This retrospective study aimed to evaluate the effect of low-dose aspirin (50-150 mg/d) on the severity of ischemic colitis.Materials and Methods: A total of 244 patients admitted to our hospital for ischemic colitis between 2013 and 2018 were included in the study. Patients were divided into two groups—aspirin and non-aspirin groups—based on their recent history of aspirin use before the onset of ischemic colitis. Clinical performance, biochemical indices, and endoscopic findings were compared.Results: The average age and the proportion of underlying disease, including hypertension, cerebral infarction, and coronary heart disease in the aspirin group was significantly higher than those in the non-aspirin group (p<0.05). In terms of clinical symptoms, the proportion of diarrhea in the aspirin group was significantly higher than that in the non-aspirin group, while the proportion of abdominal pain was significantly lower in the aspirin group compared with the non-aspirin group. Colonoscopy results showed that the incidence of ulceration was significantly higher in the aspirin group than in the non-aspirin group (p<0.05).Conclusion: The use of low-dose aspirin may aggravate the severity and mask the symptoms of abdominal pain in ischemic colitis.Cite this article as: Xiao W, Zhou Y, Wu K, et al. Low-dose aspirin and the severity of ıschemic colitis: A single-center retrospective study. Turk J Gastroenterol 2020; 31(12): 848-52.